Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1016/s0092-8674(02)00651-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Subcellular mRNA Localization

Abstract: Localization of RNA is a widespread and efficient way to target gene products to a specific region of a cell or embryo. This strategy of posttranscriptional gene regulation utilizes a variety of distinct mechanisms to regulate the movement and anchoring of different transcripts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
245
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(260 citation statements)
references
References 91 publications
7
245
1
7
Order By: Relevance
“…Au cours des deux dernières décennies, des ARNm localisés ont été impliqués dans une variété de processus biologiques associés à la polarisation cellulaire, incluant la formation de gradients morphogénétiques, la spé-cification des axes embryonnaires, la division cellulaire asymétrique, et la migration cellulaire [1][2][3][4]. Malgré ces nombreux exemples, il est communément admis que la localisation des ARNm à un endroit restreint de la cellule représente un phénomène rare et limité à des transcrits spéciali-sés.…”
Section: Localisation Subcellulaire Des Arnmunclassified
See 1 more Smart Citation
“…Au cours des deux dernières décennies, des ARNm localisés ont été impliqués dans une variété de processus biologiques associés à la polarisation cellulaire, incluant la formation de gradients morphogénétiques, la spé-cification des axes embryonnaires, la division cellulaire asymétrique, et la migration cellulaire [1][2][3][4]. Malgré ces nombreux exemples, il est communément admis que la localisation des ARNm à un endroit restreint de la cellule représente un phénomène rare et limité à des transcrits spéciali-sés.…”
Section: Localisation Subcellulaire Des Arnmunclassified
“…La vision traditionnelle suggère que la localisation des protéines est principalement déterminée après leur synthèse, grâce à des séquences peptidiques intrinsèques reconnues par des machineries de localisation spécialisées. Une alternative existe, qui implique la localisation des transcrits d'ARN messagers (ARNm), avant que ceux-ci ne soient traduits par les ribosomes [1][2][3]. Ce processus offre plusieurs avantages pour la cellule.…”
unclassified
“…The perfect example is the discovery and the studies of the function of localized RNAs. The first localized mRNAs were discovered over 2 decades ago in the oocytes of Drosophila fly and Xenopus frog (Rebagliati et al, 1985;Frigerio et al, 1986); then over 100 different localized RNAs have been found in unicellular organisms and in various cell types of animal and plant species (Bashirullah et al, 1998;King et al, 1999;Lipshitz and Smibert, 2000;Jansen, 2001;Kloc et al, 2001Kloc et al, , 2002Zhou and King, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest and most widely accepted explanations for the biological function of mRNA localization phenomenon include: (1) to assure the high-level synthesis of protein encoded by localized mRNA at the site where it is needed the most and (2) to prevent the protein from being synthesized in the region of the cell where it is not needed or could have a harmful effect (Bashirullah et al, 1998;King et al, 1999;Lipshitz and Smibert, 2000;Jansen, 2001;Kloc et al, 2002). Thus, the assumption has always been that the only function of mRNA (localized and unlocalized) is to make a protein.…”
Section: Introductionmentioning
confidence: 99%
“…Untranslated AUGs and stable secondary structures in the 5Ј UTR affect translation initiation (Pickering and Willis, 2005), and sequence-specific binding of proteins to elements in both 5Ј and 3Ј UTRs can affect degradation, polyadenylation, and mRNA localization (Wickens et al, 1997;Kloc et al, 2002). Especially during embryonic development, there is a wealth of examples of 3Ј UTRs and polyadenylation events influencing translation efficiency (Seydoux, 1996;Kuersten and Goodwin, 2003).…”
Section: Introductionmentioning
confidence: 99%